Production and Evaluation of Particleboards Made of Coconut Fibers, Pine, and Eucalyptus using Bicomponent Polyurethane-Castor Oil Resin - Bispo, Rodrigo Andraus [UNESP]; Trevisan, Mariana Ferreira [UNESP]; da Silva, Sérgio Augusto Mello [UNESP]; Aquino, Vinícius Borges de Moura; Saraiva, Raísse Layane de Paula; Arroyo, Felipe Nascimento; Molina, Julio Cesar [UNESP]; Chahud, Eduardo; Branco, Luiz Antonio Melgaço Nunes; Panzera, Túlio Hallak; Lahr, Francisco Antonio Rocco; Christoforo, André Luis (BioResources, 2022)
This research examined the influence of the compositions between coconut fiber (Cocos nucifera) and wood particles (Pinus taeda L. and Eucalyptus saligna) on physico-mechanical properties of homogeneous particleboards. The exploratory study was carried out under Tukey's contrast test of means, at 5% significance level, with the following compositions: 100% coconut fiber (F100 P0 E0); 50% coconut fiber, 25% pine particles, and 25% eucalyptus particles (F50 P25 E25); and 50% of pine particles and 50% of eucalyptus particles (F0 P50 E50), with particle moisture content between 0% to 2% and 10%, in mass, of polyurethane-castor oil (PU-Castor) resin. Three panels were produced for each composition. The physico-mechanical properties such as density, moisture content, swelling in thickness after 24 h of immersion in water, perpendicular tensile strength, static bending strength, and modulus of elasticity were evaluated using standard methods. The results obtained indicated the potential for using coconut fiber for the production of homogeneous particleboards in view of the minimum criteria required by the normative documents, with emphasis on the physical property of swelling after 24 hours, which obtained a statistically equivalent average relative to the treatment that contained only wood particles.
Keywords: Castor oil based polyurethane resin; Cocos nucifera; Particleboards; Physico-mechanical properties